Evaluation of Medication Safety Practices Among Pharmacists in A Teaching Hospital in South-East Nigeria - Afam Kanayo Udeozo; Brian Ogbonna (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2023)
The study evaluated the practice of Medication Safety and assesses the knowledge of medication safety practices among hospital pharmacists in a teaching hospital in southeast Nigeria. It was a quantitative study divided broadly into two phases. Phase one involved the collection of the medication error forms filled by pharmacists in the hospital over 3 months; January – March 2021. The second phase was the administration of self-completed questionnaires. The data was collected and analyzed. The medication errors encountered were assessed, classified, and the prevalence determined. Descriptive statistics were used to summarise the data. Overall, 68 medication error forms were collected over the 3-month data collection period. The top category of prescribing error was dose/frequency omitted (24.65%), followed by duration/stop date omitted and dose inappropriate (over), both were 17.81%. The medication safety domain to which pharmacists demonstrated the highest positive response rate (PRR) was Personal Influence Over Safety with 63.33% (SD±20.09), and the domain with the lowest positive response rate was Facilitators and Barriers at the Workplace with 46.25% (SD±25.67). Most of the pharmacists answered yes to having filled out the hospital’s medication error form at least once. 3 of the 4 medication safety domains had above-average positive response rates (PRR). The medication safety domain with the lowest PRR was the facilitators and barriers at the workplace domain with 46.25%. There were no significant differences in associations between pharmacists of different ages, years of experience, and different genders in their attitudes toward medication safety; after applying Pearson’s correlation test.